DEVELOPING BLENDED LEARNING MODEL USING SCHOOLOGY-BASED FLIPPED CLASSROOM ROTATION FOR PRACTICING SELF-REGULATED LEARNING ABILITY - Alvin Nadiroh; Ahmad Lubab; Aning Wida Yanti (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
This research is aimed to develop lesson plan (RPP) with a blended learning model in rotation of flipped classrooms and teaching materials packed into schoology to practice self-regulated learning skills in a valid and practical application. The form of the lesson plan integrates self-regulated learning aspects into learning activities to practice the students’ self-regulated learning skills. The learning material is arranged into two types: interesting reading books in PDF and animated PPT (Ms.PowerPoint) slides. The whole of the materials, discussions, and exercises are included in schoology. The topics discussed in this research are sine and cosine rules. The research applies the 4D (Define, Design, Develop, Disseminate) model of research and development. The subjects of the research are 38 students of X Science 5 of MAN 2 Gresik. The data of the research is collected by field-note and validation sheets, then analyzed with the field-note data analysis techniques, validity, and practicality of the learning media. The result of the research shows that the developed lesson plan is reached the eligibility standard based on the validity and practicality of the learning media. The validity score of the lesson plan is 4,52 on average with the highly valid category, and the validity score of learning materials in schoology is 4,48 with the highly valid category. The experts stated that the lesson plans and teaching materials in schoology that were developed were feasible with an average value of